From Political Parties to Cultural Organizations : Indonesian Islamic Movements during the New Order - Rosidi, Imron (Journal of Al-Tamaddun, 2022)
The development of political Islam in Indonesia has been characterized by severe tension between Muslim intellectuals and ‘secular’ intellectuals. Since Indonesian independence to the Old Order, Muslim intellectuals focused on struggling the political Islam by establishing political parties and proposing Islam as the state foundation. This article aims to describe political Islam in the Indonesian New Order. This article uses historical approach and qualitative methods. In fact, the New Order regime had a negative view of political Islam. This view follows from its policy which prohibited Islamic parties. The New Order emphasized national stability, as well as economic development, as its main policies. The economic development under the New Order regime led to a new crop of Muslim intellectuals. This new generation of Muslim intellectuals was different from the older generation. They preferred strengthening their role in non-political organizations to playing a role in political parties.